Tribo-characterization of natural fibre-reinforced polymer composite material - El-Tayeb, N S M (PROFESSIONAL ENGINEERING PUBLISHING LTD, 2008)
In this study, low-cost polymeric composite materials using sugarcane fibre-reinforced polyester (SCRP) with two forms of fibre reinforcement-chopped fibres (C-SCRP) and unidirectional fibres-were developed and evaluated. Interfacial adhesion between single sugarcane fibre (SSCF) and polyester, tensile properties of SSCF, and mechanical and tribological performance of SCRP composites were determined. Despite a good degree of interfacial adhesion between the SSCF and matrix, the tensile strength of the C-SCRP composite was lower compared with that of neat polyester. However, the compressive strength of the composite improved by about 37 per cent, whereas tensile and compressive moduli improved by 132 and 17 per cent, respectively. In addition, wear tests revealed that the SCRP composite is a promising material for adhesive wear applications.